Pengaruh Kualitas Layanan, Kepuasan Pelanggan, Citra Perusahaan Terhadap Loyalitas Pelanggan - Achmad Fauzi; Iwan Setyawan; Syifa Aulia; Nunti Harnanti; Anastasia Linda; Surya Opusunggu (Prisani Cendekia, 2022)
The level or frequency of customer satisfaction with the products/services they use for various reasons, including the desire to be pampered with good quality, taste and service, is known as Customer Loyalty. This article reviews the influence of Customer Loyalty, namely: Service Quality, Customer Satisfaction and Corporate Image. The author of this article aims to develop hypotheses about the effect of variables on each other to be used in further research. The results of this literature review article are: 1) Service Quality on Customer Loyalty, 2) Customer Satisfaction on Customer Loyalty; and 3) Corporate Image of Customer Loyalty